Adipokinetic hormone (Pyrap-AKH) enhances the effect of a pyrethroid insecticide against the firebug Pyrrhocoris apterus - Kodrík, Dalibor; Bártů, Iva; Socha, Radomír (Pest management science, 2010)
BACKGROUND: Adipokinetic hormones (AKHs) are insect neuropetides controlling stress situations including those elicited by insecticide treatment. The effect of Pyrap-AKH on the mortality of the firebug Pyrrhocoris apterus (L.) treated with the insecticide permethrin (Ambush 25 EC) was studied. RESULTS: Coinjection of 50 ng permethrin with 80 pmol Pyrap-AKH induced a significant 2.3-fold increase in bug mortality compared with the insecticide alone. The results were confirmed by topical coapplication of both agents (400 ng and 80 pmol respectively). Injections of 50 and 100 ng permethrin elicited a significant increase in the AKH level in CNS and the haemolymph. The results indicate an involvement of AKH in stress response to permethrin. The enhanced effect of insecticide by AKH treatments probably results from the stimulatory role in bug metabolism: carbon dioxide production was increased 3.5- and 2.5-fold respectively 1 and 3 h after permethrin treatment, and 4.3- and 3.4-fold after the permethrin plus AKH cotreatment, compared with the control. CONCLUSION: The elevation of metabolism could intensify the permethrin action by its faster penetration into tissues and by stimulation of biochemically active cells, and could be a reason for enhanced action of permethrin after its cotreatment with Pyrap-AKH.
Keywords: pesticidoví synergisté; hmyzí hormony; Pesticide Synergists; Pyrrolidonecarboxylic Acid; Oligopeptides; permethrin; Carbon Dioxide; Stress, Physiological; mužské pohlaví; oligopeptidy; Central Nervous System; Insecticides; Permethrin; fyziologický stres; Hemolymph; oxid uhličitý; hemolymfa; centrální nervový systém; ženské pohlaví; zvířata; kyselina pyrrolidonkarboxylová; Heteroptera; insekticidy; Insect Hormones; Female; Male; Animals